Effects of intensity and duration in aerobic high-intensity interval training in highly trained junior cross-country skiers - Sandbakk, O.; Sandbakk, S. B.; Ettema, G.; Welde, B. (The Journal of Strength and Conditioning Research, 2013)
The purpose of this study was to test whether a long duration of aerobic high-intensity interval training is more effective than shorter intervals at a higher intensity in highly trained endurance athletes. The sample comprised of 12 male and 9 female, national-level, junior cross-country skiers (age, 17.5 ± 0.4 years, maximal oxygen uptake (VO2max): 67.4 ± 7.7 ml/min/kg), who performed 8-week baseline and 8-week intervention training periods on dry land. During the intervention period, a short-interval group (SIG, n = 7) added 2 weekly sessions with short duration intervals (2- to 4-minute bouts, total duration of 15-20 minutes), a long-interval group (LIG; n = 7) added 2 weekly sessions with long duration intervals (5- to 10-minute bouts, total duration of 40-45 minutes). The interval sessions were performed with the athletes' maximal sustainable intensity. A control group (CG; n = 7) added 2 weekly sessions with low-intensity endurance training at 65-74% of maximal heart rate. Before and after the intervention period, the skiers were tested for time-trial performance on 12-km roller-ski skating and 7-km hill run. VO2max and oxygen uptake at the ventilatory threshold (VO2VT) were measured during treadmill running. After the intervention training period, the LIG-improved 12-km roller ski, 7-km hill run, VO2max, and VO2VT by 6.8 ± 4.0%, 4.8 ± 2.6%, 3.7 ± 1.6%, and 5.8 ± 3.3%, respectively, from pre- to posttesting, and improved both performance tests and VO2VT when compared with the SIG and the CG (all p < 0.05). The SIG improved VO2max by 3.5 ± 3.2% from pre- to posttesting (p < 0.05), whereas the CG remained unchanged. As hypothesized, a long duration of aerobic high-intensity interval training improved endurance performance and oxygen uptake at the ventilatory threshold more than shorter intervals at a higher intensity.